1993
DOI: 10.1002/ajmg.1320470525
|View full text |Cite
|
Sign up to set email alerts
|

MIDAS syndrome (microphthalmia, dermal aplasia, and sclerocornea): An X‐linked phenotype distinct from Goltz syndrome

Abstract: Bilateral microphthalmia with blepharophimosis, linear lesions of dermal aplasia involving the face, and microcephaly were present in a newborn girl who died at age 9 months from cardiomyopathy resulting in ventricular fibrillation. Autopsy showed an atrial septum defect, persistent gross trabeculation of the left ventricle, and an arteria lusoria. This case represents a further example of a new entity for which we propose the term MIDAS syndrome. The acronym stands for microphthalmia, dermal aplasia, and scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 13 publications
3
79
0
1
Order By: Relevance
“…The MIDAS syndrome [14] on the contrary shows skin features which resemble the skin changes in IP (table 2). Here, however, the ocular involvement is very different: in the MIDAS syndrome there is microphthalmia, very often corneal opacities, secondary glaucoma and orbital cysts.…”
Section: Differential Diagnosis To Other Hereditary Dermatoses With Omentioning
confidence: 99%
See 1 more Smart Citation
“…The MIDAS syndrome [14] on the contrary shows skin features which resemble the skin changes in IP (table 2). Here, however, the ocular involvement is very different: in the MIDAS syndrome there is microphthalmia, very often corneal opacities, secondary glaucoma and orbital cysts.…”
Section: Differential Diagnosis To Other Hereditary Dermatoses With Omentioning
confidence: 99%
“…Other dominantly inherited disorders which affect the skin and eye simultaneously are the NFS syndrome (Naegeli-Franceschetti-Jadassohn syndrome) and the MIDAS syndrome (microphthalmia-dermal aplasia-sclerocornea syndrome), the latter of which is transmitted in an Xlinked autosomal way as well (tables 1, 2 [14,17].…”
Section: Differential Diagnosis To Other Hereditary Dermatoses With Omentioning
confidence: 99%
“…For example, skin lesions are limited to the face and neck in MLS syndrome and skeletal abnormalities, such as clefting of hands or feet, and syndactyly are only present in patients with FDH. 8,9 Recently, the underlying genetic defects of FDH and MLS syndrome have been identified. Heterozygous mutations in the HCCS gene (Xp22.2), encoding the mitochondrial holocytochrome c-type synthase are responsible for MLS.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic variations are significant and some patients possess only one of the two major anomalies. To date, 22 affected individuals have been reported (Ropers et al 1982;Al-Gazali et al 1988;Donnenfeld et al 1990;Temple et al 1990;Allanson and Richter 1991;Gericke et al 1991;Thies et al 1991;Lindor et al 1992;Naritomi et al 1992;Happle et al 1993;Schaefer et al 1993;1996;Bird et al 1994;Eng et al 1994;Lindsay et al 1994;Mucke et al 1995;Stratton et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic studies of MLS syndrome have revealed a variety of sexchromosome aberrations, including del Xp22 (-pter) in 11 female patients, translocation between the X and an autosomal chromosome in five female patients, X;Y translocation in four female patients, 46,XX in two female patients, of whom one did not undergo high-resolution analysis (Happle et al 1993) and the other with a normal karyotype who did (Bird et al 1994), as well as two XX male patients. Recent molecular investigations of Xp microdeletions in MLS syndrome have detailed the critical region of the genetic map 1996).…”
Section: Introductionmentioning
confidence: 99%